Effects of Dietary Management Education on Self-Efficacy and Caregiver Practice in Dietary Care of Family Members with Type 2 DM - Ria Anggraini; Chriswardani Suryawati; Nurullya Rachma (Alma Ata University Press, 2018)
Type 2 Diabetes Mellitus (DM) is one of the public health problems with high prevalence both in Indonesia and in the word. According to the World Health Organization (2016), 90% of all DM cases around the world is of type 2 DM. Data from the Indonesian Ministry of Health in 2014 also showed that 90% of all diabetic cases in Indonesia were of type 2 DM. In caring for the family members with type 2 DM, caregivers require self-efficacy and practice of dietary care. This self-efficacy and care practice can be improved through dietary management education. This study aimed to analyze the effects of type 2 DM dietary management education on self-efficacy and dietary care practice of caregivers. This quantitative study used a pre and posttest quasi-experimental design with a control group. The samples were 44 caregivers recruited using purposive sampling technique and were assigned to two groups based on the inclusion and exclusion criteria. The results showed that dietary management education could improve self-efficacy and caregiver practice in the dietary care of family members with type 2 DM (p-value=0.000 and α=0.05). This study concluded that type 2 DM dietary management education program gave effects on self-efficacy and caregiver practice. Dietary management education can be used as an alternative to improve self-efficacy and caregivers’ practice in the dietary care of patients with type 2 DM.